Technology Acceptance Behavior and Feedback Loop: Exploring Reverse Causality of TAM in Post-COVID-19 Scenario - Ishaq, Erum; Bashir, Sajid; Zakariya, Ramsha; Sarwar, Aisha (Frontiers in Psychology, 2021)
In this paper we considered reverse causality of technology acceptance model, specifically in post-COVID-19 scenario. We propose a theoretical model that considers impact of technology acceptance behaviors after COVID-19over user’s beliefs in terms of perceived ease of using technology and its usefulness. More specifically we suggested that acceptance of technology post-COVID-19, may have influenced many technology related individual factors such as users’ computer efficacy, mastery experience and self regulated learning while using technology that in turn may have affected users’ beliefs in relation to ease of using technology. Such an effect is ultimately reflected in users’ belief of technology usefulness and favourable post-COVID-19 attitude towards using technology. We further extend our model to identify individuals’ mastery orientation that may moderate the relationship between technology acceptance behaviors and favourable attitude towards using technology in post-COVID-19 scenario. Both practical and theoretical implications of this perspective are discussed.